Flipped Classroom in teaching nursing management: experience report - Jouhanna do Carmo Menegaz; Geyse Aline Rodrigues Dias; Ricky Falcão Silva Trindade; Suzayne Naiara Leal; Nathalia Karym Araújo Martins (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To report the experience of the use of two Flipped Classroom methods in the curricular activity of the Health Services Organization of an undergraduate nursing course. Method: Report of teaching experience developed in the second half of 2016 and the first 2017 through the introduction of Just in Time Teaching and Peer Instruction into three programmatic content. Results: The flipped methods were introduced into two classes. Peer Instruction and Just in Time Teaching were introduced in class one, in organizational alignment classes and administrative process, respectively. In class two, only Just in Time Teaching, in labour process and administrative process classes. Conclusion: Students had difficulty integrating the individual study. Isolated insertion initiatives may hinder teacher planning and pedagogical structuring of content approach.